Perspektif Siswa terhadap Penggunaan Google Classroom sebagai Media Pembelajaran - Aprilia P; Aminah Suriaman; Darmawan Darmawan; Jamilluddin Jamilluddin; Mukrim Mukrim (Jurnal Kreatif Online, 2022)
This research intends to analyze the student’s perspective of the use of Google Classroom as an instructional medium. The research is descriptive qualitative. This research was conducted at SMA Karuna Dipa Palu. The participants of this research were a total of 20 students in the science and social class of the 2020/2021 academic year. They were selected by using the purposive sampling technique. The data collection employed triangulation by using semi-structured questionnaires and semi-structured interviews. The findings of the research revealed that the students’ perceptions on the implementation of Google Classroom as an instructional medium are acceptable. Google Classroom helps the students to be productive and facilitates the teaching and learning process during the Covid-19 pandemic. There two obstacles faced by students during the implementation of Google Classroom are the internet connection and electricity instability. Even though the students faced some obstacles during the implementation of Google Classroom, the students perceived that Google Classroom is beneficial and effective for instructional medium.